Caspase-3C gene from red swamp crayfish, Procambarus clarki: Characterization and expression in response to pathogenic infection. Issue 94 (November 2019) - Chen, Yu-Lei; Han, Keke; Huang, Xin; Zhang, Zhuoxing; Wan, Xihe; Ren, Qian
Abstract: The caspase is an essential module in the Drosophila immune deficiency (IMD) pathway, which plays a crucial role in countering pathogen infection. In this study, a gene named PcCaspase-3C was found in Procambarus clarkia with a full-length of 4684 bp, including a 1572 bp opening reading frame, which encoded a putative protein of 523 amino acids. PcCaspase-3C contained a CASc domain constituted of 237 amino acids. The PcCaspase-3C gene was primarily expressed in heart, stomach, and intestine, while less in gonad, hepatopancreas, gills, and hemocytes, with the least expression in muscle. Infection with Staphyloccocus aureus, Vibrio parahaemolyticus or white spot syndrome virus (WSSV) induced an up-regulated expression of PcCaspase-3C in intestine or stomach to varying degrees. When PcCaspase-3C was silenced by double-stranded RNA, the expression of some antimicrobial peptides such as ALF2, ALF5, ALF6, Cru3, Cru4, and Lys was significantly inhibited. In addition, silencing of PcCaspase-3C accelerated infection with WSSV in vivo . According to these results, we suggest that PcCaspase-3C might play a crucial role in the immune response of P. clarkia against pathogenic bacterial and viral infections. Highlights: PcCaspase-3C was identified in Procambarus clarkia with a full-length of 4684 bp. Pathogenic infection induced an up-regulated expression of PcCaspase-3C in intestine or stomach. PcCaspase-3C regulated the expression of some antimicrobial peptides. Silencing of PcCaspase-3C accelerated WSSV infection in vivo.